1993
DOI: 10.1039/c39930000238
|View full text |Cite
|
Sign up to set email alerts
|

Small depsipeptides as solvent gelators

Abstract: The formation of very thermostable gels with several solvents is reported for two cyclic depsipeptides o f comparatively low molecular mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 8 publications
(1 reference statement)
2
44
0
2
Order By: Relevance
“…[3] We have been interested in the gelation of organic solvents induced by small organic molecules and in the way that gelation phenomena are coupled with the formation of large supramolecular assemblies. [4] However, the structures of such gels are poorly understood, and serendipity appears to have been the major guiding principle in this particular area. [4,5] Most of the gelating molecules known so far possess at least one moiety that can participate in highly directional noncovalent interactions with other gelator molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] We have been interested in the gelation of organic solvents induced by small organic molecules and in the way that gelation phenomena are coupled with the formation of large supramolecular assemblies. [4] However, the structures of such gels are poorly understood, and serendipity appears to have been the major guiding principle in this particular area. [4,5] Most of the gelating molecules known so far possess at least one moiety that can participate in highly directional noncovalent interactions with other gelator molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, the structures of such gels are poorly understood, and serendipity appears to have been the major guiding principle in this particular area. [4,5] Most of the gelating molecules known so far possess at least one moiety that can participate in highly directional noncovalent interactions with other gelator molecules. Aggregation of these molecules can, for instance, lead to extended one-dimensional arrays of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of the developed BML enzymatic assay was the possibility of analysing up to 20 samples per hour, both for D-and L-lactate. In comparison, capillary electrophoresis, which can detect six different analytes in the same sample, allows the determination of only four samples per hour, without resolution of D-and L-lactate [9]. No significant interferences for the lactate sensor were found.…”
Section: Lactate Assay In Beermentioning
confidence: 99%
“…Several highly sophisticated methods, both chromatographic and electrophoretic, have been used to determine lactic acid in beer [7][8][9]. However they need pretreatment of samples to be analysed and they can not distinguished between lactate isomer forms.…”
Section: Introductionmentioning
confidence: 99%
“…From transmission electron microscopy (TEM) it was found that the gel consists of a network of fibers. The depsipeptide 14 was found to gelate a few solvents, among which polar (MeCN) and apolar (Et 2 O) solvents [22]. Because 14 does not dissolve in these solvents, a pre-solubilization step with a droplet of methanol is required.…”
Section: Figure 4 Amide and Carbohydrate Containing Gelatorsmentioning
confidence: 99%